2008
DOI: 10.1111/j.1468-2850.2008.00134.x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of telephone-administered psychotherapy on symptoms of depression and attrition: A meta-analysis.

Abstract: Increasingly, the telephone is being used to deliver psychotherapy for depression, in part as a means to reduce barriers to treatment. Twelve trials of telephone-administered psychotherapies, in which depressive symptoms were assessed, were included. There was a significant reduction in depressive symptoms for patients enrolled in telephone-administered psychotherapy as compared to control conditions (d = 0.26, 95% confidence interval [CI] = 0.14-0.39, p < .0001). There was also a significant reduction in depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
210
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 200 publications
(221 citation statements)
references
References 50 publications
9
210
2
Order By: Relevance
“…Research on telephonic psychotherapeutic interventions for depression reveal attrition rates of less than 10% [24]. As such, the higher dropout rate in PGAPTel cannot be attributed solely to the mode of treatment delivery.…”
Section: Original Researchmentioning
confidence: 98%
See 1 more Smart Citation
“…Research on telephonic psychotherapeutic interventions for depression reveal attrition rates of less than 10% [24]. As such, the higher dropout rate in PGAPTel cannot be attributed solely to the mode of treatment delivery.…”
Section: Original Researchmentioning
confidence: 98%
“…Although efforts to systematically evaluate the effectiveness of PGAP-Tel have only recently been initiated, there are a number of research studies that have supported the effectiveness of psychosocial interventions delivered by telephone [22,23,39]. Telephonic interventions have been shown to be effective in the treatment of depression, to maximize adherence to treatment regimens, and for follow-up management of individuals being treated for substance abuse [2][3][4]12,24].…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis conducted by Mohr et al showed significant reductions in depressive symptoms across all assessment periods among individuals who engaged in telephone-administered psychotherapy compared to usual care [29]. Comparable results were also reflected in the accuracy of diagnosis.…”
Section: Telemedicine As a Clinical Optionmentioning
confidence: 92%
“…Internet-delivered interventions overcome some barriers associated with traditional treatment methods [13]. Meta-analyses have demonstrated positive results with iCBT for depression [14,15].…”
Section: Internet-delivered Interventionsmentioning
confidence: 99%